Outcomes of rituximab‐BEAM versus BEAM conditioning regimen in patients with diffuse large B cell lymphoma undergoing autologous transplantation. Issue 10 (12th February 2020) - Jagadeesh, Deepa; Majhail, Navneet S.; He, Yizeng; Ahn, Kwang W.; Litovich, Carlos; Ahmed, Sairah; Aljurf, Mahmoud; Bacher, Ulrike; Badawy, Sherif M.; Bejanyan, Nelli; Cairo, Mitchell; Cerny, Jan; et al.
Abstract : Background: Although rituximab‐based high‐dose therapy is frequently used in diffuse large B cell lymphoma (DLBCL) patients undergoing autologous hematopoietic cell transplantation (auto‐HCT), data supporting the benefits are not available. Herein, we report the impact of rituximab‐based conditioning on auto‐HCT outcomes in patients who have DLBCL. Methods: Using the Center for International Blood and Marrow Transplant Research (CIBMTR) registry, 862 adult DLBCL patients undergoing auto‐HCT between 2003 and 2017 using BEAM (BCNU, etoposide, cytarabine, melphalan) conditioning regimen were included. All patients received frontline rituximab‐containing chemoimmunotherapy and had chemosensitive disease pre‐HCT. Early chemoimmunotherapy failure was defined as not achieving complete remission (CR) after frontline chemoimmunotherapy or relapse within 1 year of initial diagnosis. The primary outcome was overall survival (OS). Results: The study cohort was divided into 2 groups: BEAM (n = 667) and R‐BEAM (n = 195). On multivariate analysis, no significant difference was seen in OS ( P = .83) or progression‐free survival (PFS) ( P = .61) across the 2 cohorts. No significant association between the use of rituximab and risk of relapse ( P = .15) or nonrelapse mortality ( P = .12) was observed. Variables independently associated with lower OS included older age at auto‐HCT ( P < .001), absence of CR at auto‐HCT ( P < .001) and early chemoimmunotherapy failure ( P < .001). Older age ( P < .0002) and non‐CR pre‐HCT ( P < .0001) were also associated with inferior PFS. There was no significant difference in early infectious complications between the 2 cohorts. Conclusion: In this large registry analysis of DLBCL patients undergoing auto‐HCT, the addition of rituximab to the BEAM conditioning regimen had no impact on transplantation outcomes. Older age, absence of CR pre auto‐HCT, and early chemoimmunotherapy failure were associated with inferior survival. Abstract : Using Center for International Blood and Marrow Transplant Research registry data, we demonstrate that in diffuse large B cell lymphoma patients undergoing autologous hematopoietic cell transplantation, the addition of rituximab to the BEAM (BCNU, etoposide, cytarabine, melphalan) conditioning regimen has no impact on survival outcomes after transplantation.